Extensive post-transcriptional regulation revealed by integrative transcriptome and proteome analyses in salicylic acid-induced flowering in duckweed (Lemna gibba) - Fu, Lili; Tan, Deguan; Sun, Xuepiao; Ding, Zehong; Zhang, Jiaming (Frontiers in Plant Science, 2024)
Duckweed is an aquatic model plant with tremendous potential in industrial and agricultural applications. Duckweed rarely flowers which significantly hinders the resource collection and heterosis utilization. Salicylic acid (SA) can significantly induce duckweed to flower; however, the underlying regulatory mechanisms remain largely unknown. In this work, a high-quality reference transcriptome of Lemna gibba was generated using Iso-Seq strategy under SA treatment, yielding 42,281 full-length transcripts. A total of 422, 423, and 417 differentially expressed genes (DEGs), as well as 213, 51, and 92 differentially expressed proteins (DEPs), were identified at flower induction, flower initiation, and flowering stages by ssRNA-seq and iTRAQ methods.Most DEGs and DEPs were only regulated at either the transcriptomic or proteomic level. Additionally, DEPs exhibited low expression correlations with the corresponding mRNAs, suggesting that post-transcriptional regulation plays a pivotal role in SAinduced flowering in L. gibba. Specifically, the genes related to photosynthesis, stress, and hormone metabolism were mainly regulated at the mRNA level, those associated with mitochondrial electron transport / ATP synthesis, nucleotide synthesis, and secondary metabolism were regulated at the protein level, while those related to redox metabolism were regulated at the mRNA and/or protein levels. The posttranscriptional regulation of genes relevant to hormone synthesis, transcription factors, and flowering was also extensively analyzed and discussed. This is the first study of integrative transcriptomic and proteomic analyses in duckweed, providing novel insights of post-transcriptional regulation in SA-induced flowering of L. gibba.